Research on the impact of transformer switching-off on core residual magnetism - HAN Xiao; CHEN Haotian; ZHOU Jia; CHEN Wei; CHEN Deshu (Zhejiang dianli)
Magnetizing inrush current caused by transformer no-load switching can lead to various issues in power grid operations. Techniques such as phase-controlled switching are effective in mitigating these effects， with the key factor being the measurement of the transformer core’s residual magnetism. This paper investigates the impact of transformer switching-off on core residual magnetism. First， based on the transformer switching-off circuit， the switching-off interruption overvoltage is estimated， and its qualitative impact on core residual magnetism is analyzed. Next， using J-A hysteresis simulation， the relationship between transformer core residual magnetism and switching-off angle， as well as the magnetic flux trajectory after switching-off， is explored. Finally， quantitative measurement of the transformer’s residual magnetism is conducted， revealing the evolution patterns of actual residual magnetism. The theoretical analysis and simulation-based findings are validated.